Size Dependence of the Melting Temperature of Metallic Films: Two Possible Scenarios - V.M. Samsonov; N.Yu. Sdobnyakov; A.G. Bembel; D.N. Sokolov; N.V. Novozhilov (Журнал нано- та електронної фізики)
The size dependence was investigated of the melting temperature Tm of metallic films (tin and copper) on different substrate (amorphous carbon, another infusible metal), i.e. the dependence of Tm on the film thickness h. It was found that the effect of interfacial boundary can result in the growth of Tm for thin metallic films on the carbon substrate in comparison with the corresponding bulk value. For the metal 1 / metal 2 system the size dependence of Tm seems to be less pronounced and Tm decreases with decreasing thickness h.